STUDI PENGARUH HARMONISAPADAPEMILIHAN JENIS HUBUNGAN BELITAN TRANSFORMATORDAYA TIGA PHASA - Jumari Jumari; Andreas. M. Saragih (JURNAL ILMIAH TEKNIK SIPIL, 2020)
Harmonics is one of the many problems faced in the choice of transformer winding type relationships, where in a transformer there is a flux of magnetic currents due to non-linear core properties and the emergence of core losses such as hysterical losses and Eddy current losses thus resulting in power loss in the transformer. On the three-phase transformer the emergence of harmonic current waves will affect the existing magnetic flux waves, so that it can cause unwanted operations in the system. In this case from the many existing winding relationships in transformers with a delta – wye winding type connection is recommended where in the connection the delta winding can deliver harmonics current so that harmonic voltage does not arise in the system. This study provides the following results: a transformer with Delta – Wye winding type connection is recommended for use with the following considerations: 1). The amplifier current always contains harmonization components caused by losses in the transformer, 2). Delta – Wye winding connections transmit the third harmonic current, which causes harmonics voltage not to arise in the system, 3). The third harmony in the Delta – Wye winding relationship can be neutralized according to the need for a protection system.